Nivolumab-induced bullous pemphigoid managed without drug withdrawal - Mónica Munera-Campos; Adrià Plana-Pla; Noelia Rivera; Aram Boada; Carlos Ferrándiz (Wolters Kluwer Medknow Publications, 2020)
The widespread use of anti-programmed cell death receptor-1 (PD-1) agents has shed light to unusual immune-related adverse effects, especially affecting the skin. We report a case of bullous pemphigoid secondary to nivolumab therapy for metastatic renal carcinoma with a previously unreported complete response to clobetasol ointment alone. The autoimmune blistering disease was successfully treated without oral corticosteroids, and the anti-PD-1 agent could be maintained without recurrence of the skin lesions. Topical therapy remains a good option in selected, mild-to-moderate cases of induced bullous pemphigoid.